The use of balneotherapy and balnephototherapy in the treatment of psoriasis vulgaris - Grzybowski, Grzegorz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
In this paper the author reviewed medical literature for the effectiveness of balneotherapy and balneophototherapy and made a comparison of those with other modalities of treatment for psoriasis vulgaris. Although therapeutic effects are limited, balneotherapy may be proposed as an alternative therapy for psoriasis or may be used in cases of contraindications to phototherapy or systemic treatments, such as retinoids, cyclosporine or methotrexate. Narrow-band UVB (311 nm) phototherapy and salt water baths are optimal spa modalities treatment for guttate or chronic plaque type of psoriasis. Relapse rates reported here are similar to those achieved with cyclosporine and PUVA with a remarkably less potential for harmful side-effects.